Bandages for Bastet: A study of three Egyptian cat mummies - Brandt, Luise Ørsted; Hansen, Anne Haslund; Shokry, Hussein; Villa, Chiara (Archaeological Textiles Review, 2020)
Animal cults in ancient Egypt were popular especially in the Late and Greco-Roman periods, where tens of thousands of votive mummies were dedicated annually in catacombs in large necropoles. This article focuses on one of the resources required for the production of animal mummies, the textiles for bandages, in order to better understand the economic impact and organisation of animal cults. A study of three animal mummies from the National Museum of Denmark using computed tomography (CT) scanning and experimental archaeology calculated the quantities of textiles used for animal mummification. Two complete cat mummies contained entire cat skeletons while a separate head of a cat was modelled entirely from textile. The study demonstrates that at least 1 to 1.6 m2 of textiles was used to wrap a cat mummy and that therefore large quantities of textile were required for animal cults. Textiles, in addition to other resources for mummification, were in high demand at large necropoles: their evidence off ers new insights into one aspect of the complex process of mummification and emphasises the large economic and organisational scale of the animal cults.